Examining the parameters of translanguaging in the context of Chinese bilinguals' discourse practices. Issue 3 (3rd July 2022) - Fei, Yue; Weekly, Robert
ABSTRACT: This paper addresses the complexity of the linguistic situation in China by examining the language policy and language categorisation in the People's Republic of China (PRC), which has implications for how multilingual speakers conceptualise and practice 'language'. In addition, this paper examines the conceptual framework of translanguaging and its applicability to the context of an interview between speakers of Putonghua Chinese and Wu Chinese. Translanguaging has predominantly been applied to English and another language, and mainly within an educational context, therefore this paper aims to assess the extent to which the parameters of translanguaging can be extended to non-English bilingual speakers in a different context. In order to test the parameters, we consider it necessary to analyse the data using both a translanguaging framework, and a more traditional codeswitching (CS) one. While translanguaging offers the most developed theoretical understanding of multilingual discourse, there has been a tendency to elevate translanguaging into a practice which is 'new', 'creative' and 'beyond language'. We find that the discourse practices of the bilingual speakers in this study are more representative of translanguaging than CS, and provide support for the theoretical assertions attributed to translanguaging.